Risk factors and prediction model construction for poor outcome in asthma combined with severe community-acquired pneumonia in children - WANG Fanrong; ZHAO Min; LI Xiaowei; YAN Hua; LIU Xiuqin (Yixue xinzhi zazhi)
Objective To establish a nomogram prediction model and analysis the risk factors for poor outcome (PO) in children with asthma combined with severe community-acquired pneumonia (As-SCAP) to provide personalized treatment references for clinics.Methods A total of 109 As-SCAP children diagnosed from September 2019 to September 2023 in the department of pediatrics of Qingdao Municipal Hospital were retrospectively collected and divided into PO and non-PO groups according to whether PO occurred during hospitalization. Use Logistic regression analysis to determine the independent risk factors for PO, and construct a nomogram predictive model based on the regression coefficients. Receiver operating characteristic curve (ROC), calibration curve and clinical decision curve were used to evaluate the predictive ability, calibration ability and clinical net benefit of the nomogram model.Results The incidence of PO was 27.52%. Asthma attacks in recent 3 months, psychiatric symptoms, septic shock, and haemoglobin (Hb)